An Analysis of Students' Pseudo-Thinking Processes in Solving Algebra Problems from The Perspective of Self-Confidence - Nur Rahma; Mubarik; Fajriani; Pathuddin (Universitas Suryakancana, 2026)
This study aims to describe the pseudo-thinking processes of eighth-grade junior high school students in solving algebra problems, as viewed from the perspectives of high, moderate, and low levels of self-confidence. This study was conducted in the eighth grade at SMP Negeri 7 Palu during the 2025/2026 school year. A total of 3 students were selected from a group of 29 students. This research method uses a qualitative approach of a descriptive nature.The researcher employed a self-confidence questionnaire, an algebraic problem-solving test, and interviews. The results indicate that students have high self-confidence in their ability to solve problems correctly and follow problem-solving steps; however, they still struggle to explain their reasoning conceptually, suggesting that their thinking is pseudo-correct. Students with moderate self-confidence are able to solve problems fairly well, but they still make mistakes in their approach and conceptual understanding, so they tend to engage in pseudo-correct thinking, although not to the same extent as students with high self-confidence. Students with low self-confidence tend to have difficulty understanding and solving problems, leading them to give incorrect answers; however, they are able to correct their mistakes after reflecting on them, thus demonstrating pseudo-errors.